Utilização de sílica gel organofuncionalizada para adsorção de íons metálicos em solução aquosa - Cruz, ângela Maria Fagundes da (2010)
In this work the organosilanes aminopropyltriethoxysilane, 3-mercaptopropyltryethoxisilane and n[-3-(trimetoxisilyl)propyl]ethylenetriamine, as well as tetraethylortosilicate (TEOS), were employed to produce, by sol-gel method, organofuncionalized silicon samples. The prepared samples were characterized by elementar analys by thermogravimetry and infrared spectroscopy. Those samples were employed to adsorb Cd2+, Pb2+, Ni2+ and Zn2+ from aqueous solutions (10, 20, 40, 60 and 80 mg L-1). In typical experiments, 50 mg of the organometrix was suspended in 20 mL of metal cation solutions at four different contact times: 30, 60, 90 and 120 minutes. The total amount of adsorbed cations were measured by atomic absorption spectrometry. To all investigated matrices, the following adsorption capacity was observed: Ni2+ > Zn2+ > Cd2+ > Pb2+. Such sequence is closely related with the cation radius, as well as the cation hardness